The Forgotten: The Challenges Faced by Francophone Nursing Candidates following the Introduction of the NCLEX-RN in Canada. - Lalonde, Michelle (Nursing Leadership (1910-622X), 2019)
In 2015, the traditional paper-and-pencil entry-to-practice exam in Canada was replaced by a computer-adaptive testing exam, the American National Council Licensure Examination for Registered Nurses (NCLEX-RN). As there are two official languages in Canada -- English and French -- the NCLEX-RN was translated to French. Although initially the pass rates for anglophone writers with the NCLEX-RN were lower than with the previous Canadian licensing exam, their pass rates have now increased. By contrast, francophone writers have continued to have lower pass rates, and a decreasing number of candidates are choosing to write the exam in French. A lack of access to French language preparatory resources is being reported by francophone graduates as one of the contributing factors. Canadian nursing regulators report that they are not responsible for ensuring that candidates have access to preparatory materials. However, given the bilingual culture and heritage in Canada, there is a responsibility to ensure equitable access to preparatory resources to ensure success on the licensing exam. This paper raises alarm about the decreasing number of francophone graduates writing the NCLEX-RN in French and the ongoing delivery of safe, quality nursing care to francophone patients by nurses proficient in the French language.